2022
DOI: 10.1136/jech-2021-218415
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring sociodemographic inequality in COVID-19 vaccination uptake in England: a national linked data study

Abstract: BackgroundThe UK began an ambitious COVID-19 vaccination programme on 8 December 2020. This study describes variation in vaccination uptake by sociodemographic characteristics between December 2020 and August 2021.MethodsUsing population-level administrative records linked to the 2011 Census, we estimated monthly first dose vaccination rates by age group and sociodemographic characteristics among adults aged 18 years or over in England. We also present a tool to display the results interactively.ResultsOur sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 11 publications
6
33
0
1
Order By: Relevance
“…With these falls in uptake, there is concern about future immunity. These analyses confirm an observed inequality of increased vaccine refusal in younger groups living in more deprived communities [26, 27, 19]. Our analyses illustrate how these inequalities in uptake manifest as larger clusters of low uptake consistent with clustering of communities with a higher degree of deprivation, that may become more polarised as nationwide uptake falls.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With these falls in uptake, there is concern about future immunity. These analyses confirm an observed inequality of increased vaccine refusal in younger groups living in more deprived communities [26, 27, 19]. Our analyses illustrate how these inequalities in uptake manifest as larger clusters of low uptake consistent with clustering of communities with a higher degree of deprivation, that may become more polarised as nationwide uptake falls.…”
Section: Discussionsupporting
confidence: 81%
“…With these falls in uptake, there is concern about future immunity. These analyses confirm an observed inequality of increased vaccine refusal in younger groups living in more deprived communities [29, 30, 22]. Data from the second round of booster doses then suggest that this deprivation trend may become exacerbated in future rounds if uptake were to decline further, and our projections illustrate how this may manifest spatially, revealing large clusters of low uptake consistent with clustering of communities with a higher degree of deprivation.…”
Section: Discussionsupporting
confidence: 78%
“…We found that views towards COVID-19 vaccination were generally similar across ethnic groups between June and October 2020, while larger UK quantitative studies conducted within the first year after vaccine rollout demonstrated lower uptake in certain ethnic minority groups, and there were sometimes further inequalities by age, gender, religion, area deprivation, disability status, English language proficiency, socioeconomic position and educational attainment 21–24. Surveillance data demonstrate that COVID-19 vaccination rates in the UK and Israel were lowest among certain ethnic minority groups 25 26.…”
Section: Discussionmentioning
confidence: 78%
“…Attitudes, intentions and uptake We found that views towards COVID-19 vaccination were generally similar across ethnic groups between June and October 2020, while larger UK quantitative studies conducted within the first year after vaccine rollout demonstrated lower uptake in certain ethnic minority groups, and there were sometimes further inequalities by age, gender, religion, area deprivation, disability status, English language proficiency, socioeconomic position and educational attainment. [21][22][23][24] Surveillance data demonstrate that COVID-19 vaccination rates in the UK and Israel were lowest among certain ethnic minority groups. 25 26 For UK healthcare workers between December 2020 and February 2021, studies found that some ethnic minority groups were more likely to be COVID-19 vaccine hesitant in comparison with white British groups, 12 and that COVID-19 vaccine uptake was lower among some ethnic minority groups compared with white people.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Less is known about the uptake of Covid-19 vaccination among middle-aged and younger individuals. A previous study has demonstrated a lower uptake and even larger sociodemographic differences in vaccination uptake in the younger and middle-aged population than in the older population [12] . In a recent preprint addressing a working population of 40-64 years olds in England, vaccination uptake clearly differed by occupation with lower vaccination coverage in individuals working in elementary occupations, while managers and individuals in professional and administrative occupations had a higher uptake [13] .…”
Section: Introductionmentioning
confidence: 85%